Effects of sorbitol-mediated curing on the physicochemical properties and bacterial community composition of loin ham during fermentation and ripening stages - Yeling Zhou; Ying Zhou; Jing Wan; Qiujin Zhu; Linggao Liu; Sha Gu; Hongying Li (Food Chemistry: X, 2023)
In this study, the impacts of loin ham with sorbitol-mediated curing on its physicochemical properties and bacterial community composition during fermentation and ripening were investigated. The salt content, pH, and water activity (aw) were lower in the sorbitol group than in the control group throughout the fermentation and ripening stages (P < 0.05). In addition, the L* values were higher in the sorbitol group (P < 0.05). Additionally, microbial diversity diminished in all groups as the fermentation and ripening process proceeded, with Lactobacillus turning into the dominant genus in the control group and Staphylococcus and Lactobacillus becoming dominant in the sorbitol group. Pearson’s correlation analysis confirmed that the physicochemical properties have been significantly correlated with the bacterial community. In conclusion, sorbitol-mediated curing not only facilitates salt reduction while prolonging the storage period of loin ham, but also improves the distribution of bacterial community in loin ham and enhances its quality.